Talar Osteochondral Autograft Transplant. Issue 4 (December 2020) - Jorgensen, Anna; Edgar, Cory; Geaney, Lauren E.
Abstract : Osteochondral lesions of the talus vary both in terms of patient symptoms and treatment options. Patient presentation is variable, commons symptoms include minor previous trauma with persistent pain, recurrent ankle swelling, and mechanical symptoms. Treatment often depends on the stability of the cartilage fragment and typically includes a course of conservative treatment. Surgical options include simple arthroscopy with loose body removal with or without microfracture, open reduction and internal fixation of the lesion, autologous chondrocyte implantation with structural allograft, or an osteochondral autograft transplant (OAT), typically using the knee as a donor site. Although a range of successful surgical treatments has been published, OATs demonstrates reliable functional outcomes and is a good option for large osteochondral lesions (>1.5 cm 2 ), after a failed microfracture or in situations with cystic lesions. In this article, we aim to provide a comprehensive description of OAT of the talus. Level of Evidence: Diagnostic Level V. See Instructions for Authors for a complete description of levels of evidence.